Meat quality of white and natural colored male lambs raised in the Pampa Biome - Costa, Pablo Tavares; Lemes, Jaqueline Schneider; de Mendonça, Gilson; Gonçalves, Michelle; Costa, Rômulo Tavares; Vieira, Thiago Pereira (Revista Ceres, 2017)
Sheep meat quality is influenced by a number of factors either intrinsic (species, breed, sex, and age) or extrinsic (nutrition, environment, and pre- and post-slaughter handling) to the animal. However, it is not known whether wool fiber color variations within the same breed can influence the instrumental and sensory characteristics of the meat. Thus, the objective of this study was to investigate the effect of the genetic group on the instrumental and sensory characteristics of meat of white and natural colored Corriedale lambs. The 29 lambs (13 natural colored and 16 white) used in the experiments were raised on natural pasture under extensive grazing conditions in the region of the Pampa Biome, Rio Grande do Sul, Brazil. The animals were slaughtered at average age of 18 months. Meat evaluations were performed on samples from longissimus dorsi muscles. The analysis of variance was used to evaluate the effect of the genetic group and the means were compared by the F test. The instrumental analysis showed that meat of natural colored lambs had darker red color, higher 24 h pH, and higher scores for fat cover and texture. Sensory profiling was performed by nine trained panelists in four sessions. The sensory evaluation showed that natural colored lambs had darker red color, higher scores of fat taste and characteristic taste to the species. Despite significant differences in some sensory aspects, the samples were equally accepted by the panelists. Meat of natural colored Corriedale lambs had different instrumental and sensory profiles from that of white lambs.